Enhancing scabies knowledge among Indonesian boarding school students through a Wayang video - Nadyatul Husna; Anggiansyah Pohan; M. Andhika Dwi Putra; Laila Isrona; Firdawati Firdawati (PAGEPress Publications, 2024)
Skin diseases, such as scabies, present a significant global health concern, particularly among Indonesian boarding school students, resulting in complications, disruptions to daily life, and academic hindrances. To effectively address this issue, a health education approach utilizing Wayang videos was implemented, leveraging cultural elements for enhanced outcomes. Our research aimed to assess the impact of a Wayang educational video on scabies knowledge among Indonesian boarding school students. This study, conducted from October 2019 to October 2020, involved 447 students. Pre- and post-tests were administered to measure knowledge levels. Our findings demonstrate a significant improvement in scabies knowledge among students following the Wayang video education intervention. The bivariate Wilcoxon test identified a significant difference (p<0.05) in average scores before and after the educational intervention. Knowledge scores increased from 76.75 in the pre-test to 83.09 in the post-test, marking an 8.27% improvement. This study underscores the efficacy of Wayang educational video in augmenting scabies knowledge among Indonesian boarding school students, with a particular emphasis on the impact of a video titled "Malin and the Mite". This innovative cultural approach holds promise as a potential model for analogous regions, contributing to scabies prevention and advancing public health objectives.